Magnetic and transport properties of diluted granular multilayers - Silva, Hugo G. (2014)
The magnetic and transport properties of Co80Fe20t /Al2O34 nm multilayers with low nominal thicknesses t=0.7 and 0.9 nm of Co80Fe20 granular layers are studied. Magnetic studies find a superparamagnetic state above the blocking temperature Tb of field-cooled/zero-field-cooled splitting that grows with t and decreases with H. The low-voltage Ohmic tunnel transport passes to non-Ohmic IV3/2 law for applied fields above 500 V/cm. At fixed V, the temperature dependence of conductance reveals an anomalous dip around 220 K, which can be attributed to the effect of surface contamination by supercooled water. Current-in-plane tunnel magnetoresistance MR ratio tends, at lower t, to higher maximum values 8% at room temperature but to lower field sensitivity. This may indicate growing discorrelation effect e.g., between shrinking areas of correlated moments in this regime and corroborates the deficit of granule magnetization estimated from the Inoue–Maekawa MR fit, compared to that from direct magnetization measurements. MR displays a mean-field-like critical behavior when t approaches the point of superparamagnetic/ superferromagnetic transition tc1.3 nm at room temperature from below, different from the formerly reported percolationlike behavior at approaching it from above.With growing temperature, MR reveals, beyond the common decrease, an anomalous plateau from Tb30–50 K up to some higher value T150–200 K, not seen at higher t.